A CMOS-compatible Electronic Nose Fabricated via Dielectrophoretic Assembly of Nanomaterials. - MacNaughton, Sam. (2017)
Abstract: An electronic nose formed from a heterogeneous array of chemiresistors is presented. The sensor is fabricated in a novel, CMOS-compatible process by the sequential, dielectrophoretic assembly of a diverse set of chemiresistive nanomaterials (reduced graphene oxide, carbon nanotubes, and copper oxide nanowires) onto a silicon chip. Fabrication of the substrate and nanomaterials is detailed, as well is the process of sequential dielectrophoretic assembly to integrate the nanomaterials and substrate. Individually, the sensors show a high degree of sensitivity, demonstrating fractional changes of resistance of greater than 50% upon exposure to gas vapors. The entire chip with the ensemble of chemiresistors is shown to be an effective electronic nose, with distinguishable responses to ammonia, methanol, and toluene.; Thesis (M.S.)--Tufts University, 2013.; Submitted to the Dept. of Electrical Engineering.; Advisor: Sameer Sonkusale.; Committee: Tom Vandervelde, and Mehmet Dokmeci.; Keyword: Electrical engineering.